Language Parsing and Syntax of Malayalam Language - Latha R Nair and David Peter S
Parsers are integral components of many natural language processing systems for machine translation, language understanding etc. Parsers need the syntax of the language for creating the parse tree. This paper discusses the derivation of the syntax rules for sentences in Malayalam language. It also discusses the list of hierarchical syntax rules in context free grammar form. A set of part of speech tags and chunk tags were derived for representing the rules in context free grammar notation. The rule set covers the syntax of most of the commonly occurring sentences in Malayalam language.